Penaeus monodon Interferon Regulatory Factor (PmIRF) Activates IFNs and Antimicrobial Peptide Expression via a STING-Dependent DNA Sensing Pathway - Soponpong, Suthinee; Amparyup, Piti; Kawai, Taro; Tassanakajon, Anchalee (Frontiers in Immunology, 2022)
Interferon regulatory factors (IRFs) are transcription factors found in both vertebrates and invertebrates that were recently identified and found to play an important role in antiviral immunity in black tiger shrimp Penaeus monodon. In this study, we investigated the mechanism by which P. monodon IRF (PmIRF) regulates the immune-related genes downstream of the cytosolic DNA sensing pathway. Depletion of PmIRF by double-stranded RNA-mediated gene silencing significantly reduced the mRNA expression levels of the IFN-like factors PmVago1, PmVago4, and PmVago5 and antilipopolysaccharide factor 6 (ALFPm6) in shrimp. In human embryonic kidney (HEK293T) cells transfected with PmIRF or co-transfected with DEAD-box polypeptide (PmDDX41) and simulator of IFN genes (PmSTING) expression plasmids, the promoter activity of IFN-β, nuclear factor (NF-κB), and ALFPm6 was synergistically enhanced following stimulation with the nucleic acid mimics deoxyadenylic–deoxythymidylic acid sodium salt (poly(dA:dT)) and high molecular weight (HMW) polyinosinic–polycytidylic acid (poly(I:C)). Both nucleic acid mimics also significantly induced PmSTING, PmIRF, and ALFPm6 gene expression. Co-immunoprecipitation experiments showed that PmIRF interacted with PmSTING in cells stimulated with poly(dA:dT). PmSTING, PmIRF, and PmDDX41 were localized in the cytoplasm of unstimulated HEK293T cells and PmIRF and PmDDX41 were translocated to the nucleus upon stimulation with the nucleic acid mimics while PmSTING remained in the cytoplasm. These results indicate that PmIRF transduces the pathogen signal via the PmDDX41–PmSTING DNA sensing pathway to induce downstream production of interferon-like molecules and antimicrobial peptides.